Ennumeration of Wall Floras of Mahendranagar Municipality, Far West, Nepal - Dhakal, Tilmaya (Himalayan Biodiversity, 2017)
Wall floras are the plants growing on the manmade habitats such as walls, fences, buildings, temples, old walls, etc. In this study, wall floras of Mahendranagar municipality were enumerated. A total of 111 species belonging to 87 genera and 33 families of angiosperm were found within the study area. All the types of plant species like herbs, shrubs and trees are reported and among them herbs are dominant. The major wall floras associated with different walls are Ficus bengalensis, Amaranthus spionus, Solanum nigrum, Adiantum sp, Dryopteris sp, mosses and some grasses.